Honeycomb ceramic carrier for ship and preparation method

By using raw materials such as cordierite powder to prepare honeycomb ceramic carriers for ships, the problems of high porosity, thin walls and low costs in the existing technology are solved, and the high strength and low cost of the carrier are achieved, and market competitiveness and air pollution control capabilities are improved.

CN119638369APending Publication Date: 2025-03-18SHANDONG AOFU ENVIRONMENTAL PROTECTION SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510161893.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

While the existing honeycomb ceramic carriers for ships meet the emission regulations limits, it is difficult to achieve high porosity, thin walls and low costs, and the strength is insufficient, resulting in high production costs and weak market competitiveness.

Method used

Cordierite powder is used as the raw material, combined with iron oxide, graphene precursor, fruit shell powder and cellulose and other components, and honeycomb ceramic carriers with thin walls, high porosity, high strength and low cost are prepared through dry mixing, wet mixing and kneading and firing.

Benefits of technology

It realizes the comprehensive advantages of thin-wall, high porosity, high strength and low cost of honeycomb ceramic carriers, reduces manufacturing costs, improves market competitiveness, and meets the diversified needs of markets in different regions, helps to control air pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of honeycomb ceramics, in particular to a honeycomb ceramic carrier for a ship and a preparation method. The raw materials comprise a first inorganic powder material, a second inorganic powder material, an organic powder material, a lubricant and water, the first inorganic powder material comprises cordierite powder, the second inorganic powder material comprises iron oxide, and the organic powder material comprises a graphene precursor, shell powder and cellulose; the porosity of the cordierite powder is 54-57%, the median pore diameter is 17-20 microns, and the particle size D50 is 40-50 microns. The cordierite serving as a raw material can be used as a eutectic component to reduce the temperature for synthesizing the honeycomb ceramic carrier, and the cordierite serving as a seed crystal can promote the other components to synthesize the cordierite, promote crystallization and growth of crystals and increase the strength of the carrier for the high-porosity ship; the composite material has the advantages of thin wall, high porosity, high strength and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of honeycomb ceramics, and in particular to a honeycomb ceramic carrier for ships and a preparation method thereof. Background Art

[0002] As green and low-carbon goals are gradually recognized and accepted by countries around the world, the shipping industry, as a major carbon emitter, has received more and more attention and pressure. The International Maritime Organization has also formulated greenhouse gas emission reduction measures, which have officially come into effect, and the European Union has also included the shipping industry in the carbon emission control system. my country is a country with relatively rich inland shipping resources. In view of the urgent situation of air pollution prevention and control in my country's ports and ships, the Ministry of Ecology and Environment has formulated the "Ship Engine Exhaust Pollutant Emission Limits and Measurement Methods (China Phase I and II)" to strengthen the control of ship pollutant emissions and fill the gap in ship air pollution emission standards.

[0003] At present, ships use compression ignition and spark ignition engines, and the fuel used is diesel or marine fuel oil with a high sulfur content. The pollutants emitted include particulate matter (PM), nitrogen oxides (NO x ), hydrocarbons (HC), carbon monoxide (CO) and sulfur dioxide (SO2). The standards specify emission limits for the above pollutants. According to research, the level of SO2 emissions is mainly related to the sulfur (S) content of the fuel used. After combustion in the engine, almost all of the sulfur in the fuel is oxidized and converted into SO2 in the exhaust gas. Therefore, the most effective way to reduce SO2 emissions is to use fuel with a low sulfur content. x ), hydrocarbons (HC), carbon monoxide (CO), and if necessary, adopt post-treatment measures such as selective catalytic reduction device (SCR), filter, etc. Therefore, the ship engine market is large, and the development of marine honeycomb ceramic carriers can be carried out, but due to the low sales cost of the carrier, it is necessary to reduce the cost to achieve the purpose of profitability. Therefore, low-cost honeycomb ceramics are developed according to market demand.

[0004] At present, the honeycomb ceramic catalyst carriers that meet the limit standards of ship emission regulations and are widely used generally have a wall thickness of 0.5~1.0mm and a porosity of 20~50%. With the upgrading of regulations, customer needs have also diversified, and reducing the pressure drop of the post-treatment system has become one of the key technical problems. In order to increase the catalytic conversion efficiency and filtration efficiency, high pore density and high porosity carriers have become one of the market demands. In order to reduce the back pressure, the market has proposed a technical route of thin-walled and high-porosity carriers. Because, on the one hand, honeycomb ceramic products can reduce the back pressure by thinning the wall thickness, and on the other hand, by increasing the porosity, the purpose of reducing the back pressure can also be achieved. However, high porosity and thin walls are difficult to prepare, which will increase the production cost of the carrier, and the strength will be significantly reduced. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a honeycomb ceramic carrier for ships and a preparation method thereof.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: The present invention provides a honeycomb ceramic carrier for ships. The raw materials of the honeycomb ceramic carrier for ships include a first inorganic powder, a second inorganic powder, an organic powder, a lubricant and water. The first inorganic powder includes cordierite powder, the second inorganic powder includes iron oxide, and the organic powder includes a graphene precursor, nutshell powder and cellulose. The cordierite powder has a porosity of 54-57%, a median pore size of 17-20 μm, and a particle size D 50 40~50μm.

[0007] Based on the above technical solution, the present invention can also be improved as follows.

[0008] Furthermore, in the cordierite powder, the mass percentage of the cordierite phase is greater than or equal to 90%.

[0009] Furthermore, the cordierite powder is prepared from cordierite waste blanks and / or cordierite honeycomb ceramic carrier processing scraps.

[0010] Furthermore, the first inorganic powder further comprises talc, clay, alumina, and silicon dioxide, and the particle size of the talc is 50 is 40-50 μm, and the particle size D of the clay 50 The particle size D of the aluminum oxide is 1-20 μm. 50 The particle size D of the silicon dioxide is 5 to 15 μm. 50 The particle size D of the iron oxide is 5-10 μm. 50 1~10μm.

[0011] Furthermore, in the first inorganic powder, the mass percentage of each component is: cordierite powder 20wt%-100%, talc 0-34wt%, clay 0-17wt%, aluminum oxide 0-23wt%, silicon dioxide 0-11wt%. Taking the mass of the first inorganic powder as 100%, the mass percentage of the iron oxide is 5wt%.

[0012] Furthermore, taking the mass of the first inorganic powder as 100%, the mass percentages of the components in the organic powder are: 7wt% of graphene precursor, 20wt% of nut shell powder, and 6wt% of cellulose.

[0013] Furthermore, based on the mass of the first inorganic powder being 100%, the mass percentage of the lubricant is 1 wt %, and the mass percentage of water is 25 wt %.

[0014] Furthermore, the passing rate of each component of the first inorganic powder, the second inorganic powder, and the organic powder through a 150-mesh sieve is 100%.

[0015] The present invention provides a method for preparing a honeycomb ceramic carrier for ships as described above, comprising mixing the first inorganic powder, the second inorganic powder and the organic powder; adding the lubricant and water, wet-mixing, kneading and kneading to form a plastic mud segment; extruding the mud segment and drying and shaping it to obtain a green body; and sintering the green body to obtain the honeycomb ceramic carrier for ships.

[0016] Furthermore, the sintering temperature is 1290°C-1375°C.

[0017] The beneficial effects of the present invention are: (1) The honeycomb ceramic carrier for ships of the present invention uses cordierite as a raw material, so that it can be used as a low eutectic component to reduce the temperature of the synthetic honeycomb ceramic carrier, thereby achieving the purpose of reducing the manufacturing cost; (2) In the honeycomb ceramic carrier for ships of the present invention, the cordierite powder as a seed can promote the synthesis of cordierite by the other components, promote crystallization and growth of crystals, and increase the strength of the high-porosity carrier for ships; (3) The honeycomb ceramic carrier for ships of the present invention has the advantages of thin wall, high porosity, high strength and low cost; (4) The method for preparing the honeycomb ceramic carrier for ships of the present invention has low firing temperature, simple steps, low cost and high efficiency, and is suitable for wide promotion. DETAILED DESCRIPTION

[0018] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0019] The honeycomb ceramic carrier for ships of the present invention comprises raw materials including a first inorganic powder, a second inorganic powder, an organic powder, a lubricant and water, wherein the first inorganic powder comprises cordierite powder, the second inorganic powder comprises iron oxide, and the organic powder comprises a graphene precursor, nutshell powder and cellulose; wherein the cordierite powder has a porosity of 54-57%, a median pore diameter of 17-20 μm, and a particle size D 50 40~50μm.

[0020] The honeycomb ceramic carrier for ships of the present invention uses cordierite as a raw material, so that it can be used as a low eutectic component to reduce the temperature of the synthetic honeycomb ceramic carrier, thereby achieving the purpose of reducing manufacturing costs. Because the honeycomb ceramic carrier for ships is stacked and used, it is required to have a certain strength. The cordierite powder as a seed can promote the synthesis of cordierite by the remaining components, promote crystallization and growth, and increase the strength of the high-porosity ship carrier. Therefore, the present invention solves the contradictions of thin walls, high porosity, low strength and high cost of honeycomb ceramics for ships, reduces manufacturing costs, improves market competitiveness, provides guarantees for the diversified needs of the ship market, and helps the control of air pollution in lakes and oceans.

[0021] In the present invention, iron oxide is a low eutectic material and can reduce the sintering temperature.

[0022] In the present invention, the graphene precursor and the nut shell powder are pore-forming agents, which contribute to the preparation of high porosity and large median pore diameter; the cellulose is a binder, which improves the plasticity of the mud material.

[0023] Preferably, in the cordierite powder, the mass percentage of the cordierite phase is greater than or equal to 90%.

[0024] More preferably, in the cordierite powder, the mass percentage of the cordierite phase is greater than or equal to 94%.

[0025] Preferably, the cordierite powder is prepared from cordierite waste blanks and / or cordierite honeycomb ceramic carrier processing scraps; using cordierite waste blanks and processing scraps to grind into powder of a certain particle size as cordierite powder has the advantage of low cost and realizes the recycling of waste materials.

[0026] It should be noted that graphite crystal is a hexagonal plane layered structure composed of carbon elements. The carbon atoms on the layer plane are bonded by covalent bonds, and the layers are bonded by van der Waals forces. This bonding force is very weak, only about 17kJ / mol, and the interlayer distance is relatively large. Under appropriate conditions, various chemicals such as acids, alkali metals, and salts can be inserted into the graphite interlayers and combined with carbon atoms to form a new chemical phase-graphite interlayer compound. This interlayer compound can be decomposed rapidly in an instant when heated to an appropriate temperature, so that graphite expands into a worm-like new substance along the C axis direction, which is the graphene precursor used in the present invention.

[0027] Preferably, the first inorganic powder also includes talc, clay, alumina, and silica, which are all commonly used raw materials for synthesizing cordierite. 50 The particle size of clay is 40~50μm. 50 The particle size of aluminum oxide is 1~20μm. 50 The particle size of silicon dioxide is 5~15μm. 50 The particle size of iron oxide is 5~10μm.50 1~10μm.

[0028] Preferably, in the first inorganic powder, the mass percentage of each component is: cordierite powder 20wt%-100%, talc 0-34wt%, clay 0-17wt%, aluminum oxide 0-23wt%, silicon dioxide 0-11wt%. Taking the mass of the first inorganic powder as 100%, the mass percentage of iron oxide is 5wt%.

[0029] Preferably, taking the mass of the first inorganic powder as 100%, the mass percentages of the components in the organic powder are: 7wt% of graphene precursor, 20wt% of nut shell powder, and 6wt% of cellulose.

[0030] Preferably, based on 100% of the mass of the first inorganic powder, the mass percentage of the lubricant is 1 wt %, and the mass percentage of water is 25 wt %.

[0031] More preferably, the lubricant is vegetable oil, silicone oil, fatty acid amide, oleic acid, polyester, synthetic ester, carboxylic acid, etc.

[0032] Preferably, the passing rate of each component of the first inorganic powder, the second inorganic powder and the organic powder through a 150-mesh sieve is 100%.

[0033] The method for preparing the honeycomb ceramic carrier for ships of the present invention comprises the following steps: mixing a first inorganic powder, a second inorganic powder and an organic powder; adding a lubricant and water, wet-mixing, kneading and smelting to form a plastic mud segment; extruding the mud segment and drying and shaping it to obtain a green body; and sintering the green body to obtain the honeycomb ceramic carrier for ships.

[0034] Preferably, the sintering temperature is 1290°C-1375°C.

[0035] The present invention has broken through the technical difficulties in the development of high-porosity, thin-walled, low-cost, high-strength honeycomb ceramics, and has developed low-cost, high-strength honeycomb ceramics with a wall thickness as thin as 0.1 mm and a porosity as high as 60%, meeting the diversified needs of markets in different regions and contributing to the control of air pollution.

[0036] The present invention has no particular restrictions on the shape of the honeycomb grid in the structure of the honeycomb ceramic carrier. A single hole shape such as triangle, square, hexagon, etc. can be adopted, or a variety of hole shapes such as square, hexagon, asymmetric, etc. can be adopted. It is not necessary to adopt a single hole shape in the honeycomb structure, and it is preferred to adopt, for example, square holes.

[0037] The present invention has no particular limitation on the pore density of the honeycomb structure, and the pore density may be 46 cpsi, 59 cpsi, 100 cpsi, 200 cpsi, 300 cpsi, 400 cpsi, or any other pore density that can be extruded into a honeycomb shape.

[0038] The honeycomb ceramic carrier of the present invention can be mainly used as a honeycomb ceramic carrier and filter for ships, as a honeycomb ceramic carrier and filter for vehicles, and even as a water and air purifier, etc. The only difference between the preparation method of the filter and the catalyst carrier is that pore plugging and pore blocking processes are added.

[0039] The present invention is described below by means of specific examples, which are merely examples for the purpose of clear description and are not intended to limit the implementation methods.

[0040] Example 1 This embodiment adopts the method of the present invention to prepare a honeycomb ceramic carrier for ships, wherein the cordierite powder is processed by ball milling cordierite waste blanks and processing waste blanks, and the particle size of the cordierite powder is controlled to be able to pass through a 150-mesh sieve.

[0041] In this embodiment, the cordierite powder has a porosity of 54% and a median pore size of 17 μm. 50 The particle size of talc is 40 μm. 50 The particle size of the clay is 40 μm. 50 The particle size of aluminum oxide is 10 μm. 50 The particle size of silicon dioxide is 5 μm. 50 The particle size of iron oxide is 5 μm. 50 1μm.

[0042] The specific steps are as follows: 1) 20wt% cordierite powder, 34wt% talc, 12wt% clay, 23wt% alumina, 11wt% silica, 5wt% iron oxide, 7wt% graphene precursor, 20wt% nut shell powder and 6wt% cellulose were mixed evenly by a dry method.

[0043] 2) The uniformly mixed powder is kneaded with 1wt% lubricant and water to form a plastic mud segment. The amount of water added is adjusted according to the properties of the mud.

[0044] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0045] 4) The green body is fired at 1375° C. to obtain a honeycomb ceramic carrier for ships.

[0046] Example 2 This example adopts the method of the present invention to prepare a honeycomb ceramic carrier for ships, and the cordierite powder used is the same as that in Example 1.

[0047] In this embodiment, the cordierite powder has a porosity of 57% and a median pore size of 20 μm. 50The particle size of talc is 50 μm. 50 The particle size of the clay is 50 μm. 50 The particle size of aluminum oxide is 20 μm. 50 The particle size of silicon dioxide is 15 μm. 50 The particle size of iron oxide is 10 μm. 50 is 10μm.

[0048] The specific steps are as follows: 1) 40 wt% of cordierite powder, 26 wt% of talc, 9 wt% of clay, 17 wt% of alumina, 8 wt% of silica, 5 wt% of iron oxide, 7 wt% of graphene precursor, 20 wt% of nut shell powder and 6 wt% of cellulose were mixed evenly by a dry method.

[0049] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0050] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0051] 4) The green body is fired at 1365° C. to obtain a honeycomb ceramic carrier for ships.

[0052] Example 3 This example adopts the method of the present invention to prepare a honeycomb ceramic carrier for ships, and the cordierite powder used is the same as that in Example 1.

[0053] In this embodiment, the cordierite powder has a porosity of 55% and a median pore size of 18 μm. 50 The particle size of talc is 45 μm. 50 The particle size of the clay is 45 μm. 50 The particle size of aluminum oxide is 10 μm. 50 The particle size of silicon dioxide is 10 μm. 50 The particle size of iron oxide is 8 μm. 50 5μm.

[0054] The specific steps are as follows: 1) 60wt% of cordierite powder, 17wt% of talc, 6wt% of clay, 11wt% of alumina, 6wt% of silica, 5wt% of iron oxide, 7wt% of graphene precursor, 20wt% of nut shell powder and 6wt% of cellulose were mixed evenly by a dry method.

[0055] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0056] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0057] 4) The green body is fired at 1330° C. to obtain a honeycomb ceramic carrier for ships.

[0058] Example 4 This example adopts the method of the present invention to prepare a honeycomb ceramic carrier for ships, and the cordierite powder used is the same as that in Example 1.

[0059] In this embodiment, the cordierite powder has a porosity of 54.5% and a median pore size of 19 μm. 50 The particle size of talc is 44 μm. 50 The particle size of the clay is 42 μm. 50 The particle size of aluminum oxide is 8 μm. 50 The particle size of silicon dioxide is 6 μm. 50 The particle size of iron oxide is 7 μm. 50 is 6μm.

[0060] The specific steps are as follows: 1) 80 wt% of cordierite powder, 8 wt% of talc, 3 wt% of clay, 6 wt% of alumina, 3 wt% of silica, 5 wt% of iron oxide, 7 wt% of graphene precursor, 20 wt% of nut shell powder and 6 wt% of cellulose were mixed evenly by a dry method.

[0061] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0062] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0063] 4) The green body is fired at 1310° C. to obtain a honeycomb ceramic carrier for ships.

[0064] Example 5 This example adopts the method of the present invention to prepare a honeycomb ceramic carrier for ships, and the cordierite powder used is the same as that in Example 1.

[0065] In this embodiment, the cordierite powder has a porosity of 55% and a median pore size of 20 μm. 50 The particle size of iron oxide is 48 μm. 50 is 4μm.

[0066] The specific steps are as follows: 1) 100 wt% cordierite powder, 5 wt% iron oxide, 7 wt% graphene precursor, 20 wt% nut shell powder and 6 wt% cellulose were mixed evenly by dry method.

[0067] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0068] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0069] 4) The green body is fired at 1290° C. to obtain a honeycomb ceramic carrier for ships.

[0070] Example 6 This example adopts the method of the present invention to prepare a honeycomb ceramic carrier for ships, and the cordierite powder used is the same as that in Example 1.

[0071] In this embodiment, the cordierite powder has a porosity of 55% and a median pore size of 19 μm. 50 The particle size of talc is 47 μm. 50 The particle size of the clay is 48 μm. 50 The particle size of aluminum oxide is 14 μm. 50 The particle size of iron oxide is 13 μm. 50 8μm.

[0072] The specific steps are as follows: 1) 60wt% of cordierite powder, 17wt% of talc, 17wt% of clay, 6wt% of alumina, 5wt% of iron oxide, 7wt% of graphene precursor, 20wt% of nut shell powder and 6wt% of cellulose were mixed evenly by a dry method.

[0073] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0074] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0075] 4) The green body is fired at 1330° C. to obtain a honeycomb ceramic carrier for ships.

[0076] Example 7 This example adopts the method of the present invention to prepare a honeycomb ceramic carrier for ships, and the cordierite powder used is the same as that in Example 1.

[0077] In this embodiment, the cordierite powder has a porosity of 56.5% and a median pore size of 19 μm. 50 The particle size of talc is 41 μm. 50 The particle size of the clay is 41 μm. 50 The particle size of aluminum oxide is 12 μm. 50 The particle size of silicon dioxide is 7 μm.50 The particle size of iron oxide is 6 μm. 50 8μm.

[0078] The specific steps are as follows: 1) 60wt% of cordierite powder, 17wt% of talc, 9wt% of clay, 10wt% of alumina, 4wt% of silica, 5wt% of iron oxide, 7wt% of graphene precursor, 20wt% of nut shell powder and 6wt% of cellulose were mixed evenly by a dry method.

[0079] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0080] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0081] 4) The green body is fired at 1330° C. to obtain a honeycomb ceramic carrier for ships.

[0082] Example 8 This example adopts the method of the present invention to prepare a honeycomb ceramic carrier for ships, and the cordierite powder used is the same as that in Example 1.

[0083] In this embodiment, the cordierite powder has a porosity of 54% and a median pore size of 17 μm. 50 The particle size of talc is 50 μm. 50 The particle size of aluminum oxide is 40 μm. 50 The particle size of silicon dioxide is 5 μm. 50 The particle size of iron oxide is 10 μm. 50 is 10μm.

[0084] The specific steps are as follows: 1) 60wt% of cordierite powder, 18wt% of talc, 14wt% of alumina, 8wt% of silica, 5wt% of iron oxide, 7wt% of graphene precursor, 20wt% of nut shell powder and 6wt% of cellulose were mixed evenly by a dry method.

[0085] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0086] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0087] 4) The green body is fired at 1330° C. to obtain a honeycomb ceramic carrier for ships.

[0088] Comparative Example 1 In this comparative example, the particle size of each component is the same as that in Example 1, and the preparation steps are as follows: 1) 43wt% talc, 15wt% clay, 28wt% alumina, 14wt% silica, 7wt% graphene precursor, 20wt% nut shell powder and 6wt% cellulose were mixed evenly by a dry method.

[0089] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0090] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0091] 4) firing the green body at 1425° C. to obtain a cordierite honeycomb ceramic body; Comparative Example 2 In this comparative example, the particle size of each component is the same as that in Example 1, and the preparation steps are as follows: 1) 43wt% talc, 12wt% clay, 30wt% alumina, 15wt% silica, 7wt% graphene precursor, 20wt% nut shell powder and 6wt% cellulose were mixed evenly by a dry method.

[0092] 2) The uniformly mixed powder is mixed with 1wt% lubricant and water, kneaded and kneaded to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud.

[0093] 3) Extrude the plastic mud segments into a honeycomb structure and dry it to shape it.

[0094] 4) The green body is fired at 1425° C. to obtain a cordierite honeycomb ceramic body.

[0095] Comparative Example 3 In this comparative example, the source of cordierite powder is the same as that in Example 1, except that it can pass through a 300-mesh sieve. 50 The particle size of the other components is the same as that of Example 1. The preparation steps are as follows: 1) 40wt% of cordierite powder, 26wt% of talc, 9wt% of clay, 17wt% of alumina, 8wt% of silica, 7wt% of graphene precursor, 20wt% of nut shell powder and 6wt% of cellulose were mixed evenly by a dry method; 2) The uniformly mixed powder is mixed with 1wt% lubricant and water to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud; 3) Extruding the plastic mud segments into a honeycomb structure and drying and shaping; 4) The green body is fired at 1400° C. to obtain a cordierite honeycomb ceramic body.

[0096] Comparative Example 4 In this comparative example, the source of cordierite powder is the same as that in Example 1, except that it can pass through a 300-mesh sieve. 50 The particle size of the other components is the same as that of Example 1. The preparation steps are as follows: 1) 60wt% of cordierite powder, 17wt% of talc, 6wt% of clay, 11wt% of alumina, 6wt% of silica, 7wt% of graphene precursor, 20wt% of nut shell powder and 6wt% of cellulose were mixed evenly by a dry method; 2) The uniformly mixed powder is mixed with 1wt% lubricant and water to form a plastic mud segment. The amount of water added is adjusted according to the material properties of the mud; 3) Extruding the plastic mud segments into a honeycomb structure and drying and shaping; 4) The green body is fired at 1350° C. to obtain a cordierite honeycomb ceramic body.

[0097] The parameters of the above embodiments and comparative examples are shown in Table 1.

[0098] Table 1 In order to compare and analyze the advantages of the present invention, the honeycomb ceramics were extruded into a wall thickness of 0.3 mm for performance enumeration.

[0099] The compressive strength mainly evaluates the possibility of the carrier breaking during production, processing, transportation and use. Since the carriers for ships are stacked, the higher the strength, the less likely the carrier will crack during use, and the higher the yield rate during production. Thermal shock resistance mainly simulates the ability of honeycomb ceramics to resist cracking in actual harsh application environments. Porosity and median pore size mainly evaluate the ability of the catalyst to penetrate into the micropores of the carrier. The larger the median pore size and the higher the porosity, the more the catalyst can penetrate into the micropores, thereby improving the catalytic conversion efficiency.

[0100] It can be seen from the comparison of Examples 1-8 and Comparative Examples 1-4 that the use of cordierite powder significantly reduces the firing temperature of synthetic cordierite, while the strength of honeycomb ceramics is significantly increased, the yield rate is improved, and the production cost is reduced. This is because cordierite powder, as a low melting point component, can reduce the firing temperature of synthetic cordierite, and as a seed, it can promote the synthesis of new crystals and increase the strength of the carrier. Especially for honeycomb ceramic carriers, the thinner the wall thickness, the lower the strength, the higher the porosity, the lower the strength, and the lower the yield rate, the production cost will increase significantly. Therefore, the honeycomb ceramic carrier prepared by the present invention has a higher yield rate and lower production cost. In order to improve the yield rate, the pore-forming agent used in the present invention is a graphene precursor and a nutshell powder, and the decomposition temperature ranges of the two are different. The decomposition temperature of the graphene precursor is as high as 700~900℃, and the decomposition temperature of the nutshell powder is 200~450℃, which is very friendly to the yield rate of high porosity and thin-walled carriers, avoiding the concentrated heat release of the pore-forming agent to cause the carrier to crack, and can also significantly improve the yield rate.

[0101] The increase in matrix strength improves thermal shock resistance and increases the risk of cracking of thin-walled honeycomb ceramics under extremely cold and hot harsh conditions. In addition, high porosity can also provide thermal shock resistance to the carrier. This is because the increase in porosity increases the number of micropores in the honeycomb ceramic, and the material becomes loose and porous, which can buffer stress and strain under extremely cold and hot conditions, thereby ensuring that the carrier has high thermal shock resistance. The carriers of the comparative examples and comparative examples can pass 550°C thermal shock. At the same time, the use of cordierite powder and iron powder in the present invention can reduce sintering problems. At the same time, cordierite powder with a coarse particle size of 40~50μm, a large median pore size of 17~20μm, and a high porosity of 54~57% can increase the median pore size of the ship engine carrier, which is beneficial for the catalyst to penetrate into the micropore channels of the carrier, improve the catalytic conversion efficiency, and meet market demand.

[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A honeycomb ceramic carrier for ships, characterized in that: The raw materials of the honeycomb ceramic carrier for ships include a first inorganic powder, a second inorganic powder, an organic powder, a lubricant and water, wherein the first inorganic powder includes cordierite powder, the second inorganic powder includes iron oxide, and the organic powder includes a graphene precursor, nutshell powder and cellulose; wherein the cordierite powder has a porosity of 54-57%, a median pore size of 17-20 μm, and a particle size D 50 40~50μm.

2. A honeycomb ceramic carrier for ships according to claim 1, characterized in that: In the cordierite powder, the mass percentage of the cordierite phase is greater than or equal to 90%.

3. A honeycomb ceramic carrier for ships according to claim 2, characterized in that: The cordierite powder is prepared from cordierite waste blanks and / or cordierite honeycomb ceramic carrier processing scraps.

4. A honeycomb ceramic carrier for ships according to any one of claims 1 to 3, characterized in that: The first inorganic powder further comprises talc, clay, alumina, and silicon dioxide. The particle size of the talc is 50 is 40-50 μm, and the particle size D of the clay 50 The particle size D of the aluminum oxide is 1-20 μm. 50 The particle size D of the silicon dioxide is 5 to 15 μm. 50 The particle size D of the iron oxide is 5-10 μm. 50 1~10μm.

5. A honeycomb ceramic carrier for ships according to claim 4, characterized in that: In the first inorganic powder, the mass percentage of each component is: cordierite powder 20wt%-100%, talc 0-34wt%, clay 0-17wt%, aluminum oxide 0-23wt%, silicon dioxide 0-11wt%. Taking the mass of the first inorganic powder as 100%, the mass percentage of the iron oxide is 5wt%.

6. A honeycomb ceramic carrier for ships according to claim 5, characterized in that: Taking the mass of the first inorganic powder as 100%, the mass percentages of the components in the organic powder are: 7wt% of graphene precursor, 20wt% of nut shell powder, and 6wt% of cellulose.

7. A honeycomb ceramic carrier for ships according to claim 6, characterized in that: Based on the mass of the first inorganic powder being 100%, the mass percentage of the lubricant is 1wt%, and the mass percentage of water is 25wt%.

8. The honeycomb ceramic carrier for ships according to claim 4, characterized in that: The passing rate of each component of the first inorganic powder, the second inorganic powder and the organic powder through a 150-mesh sieve is 100%.

9. A method for preparing a honeycomb ceramic carrier for ships according to any one of claims 1 to 8, characterized in that: The first inorganic powder, the second inorganic powder and the organic powder are mixed; the lubricant and water are added, wet-mixed, kneaded and kneaded to form a plastic mud segment; the mud segment is extruded and dried to form a green body; the green body is fired to obtain the honeycomb ceramic carrier for ships.

10. The method for preparing a honeycomb ceramic carrier for ships according to claim 9, characterized in that: The sintering temperature is 1290°C-1375°C.

Citation Information

Patent Citations

  • Large-size diesel oil particulate filter with low pressure drop and low expansion coefficient and preparation method thereof

    CN108439967A

  • Cordierite gasoline engine particulate filter and preparation method thereof

    CN113860852A

  • Honeycomb ceramic carrier with high porosity and large aperture and preparation method thereof

    CN116023126A

  • Preparation method of honeycomb ceramic carrier capable of improving catalytic efficiency of catalyst

    CN117285376A

  • Method for producing a cordierite body

    US4476236A